'Age Matters': A panel study investigating the influence of communicative and passive smartphone use on well-being. Issue 2 (25th January 2021) - Stevic, Anja; Schmuck, Desirée; Matthes, Jörg; Karsay, Kathrin
ABSTRACT: Communicative and passive online use have been shown to affect individuals' well-being in opposite ways. While communicative use is often associated with beneficial outcomes, passive use may even harm individuals' well-being. However, existing studies have paid insufficient attention to the influence of age on these associations. Additionally, little evidence is available regarding the impact of communicative and passive smartphone use on individuals' well-being across the life-span. Drawing upon the theoretical approaches of Socioemotional Selectivity Theory, Social Convoy Model, and Social Compensation Hypothesis, we assumed that particularly communicative smartphone use may be beneficial for older adults' well-being, helping them to maintain their personal relationships. Results of a two-wave panel survey ( N T2 = 461) revealed a significant negative influence of passive smartphone use on well-being irrespective of age. In line with the Socioemotional Selectivity Theory and Social Compensation Hypothesis, communicative smartphone use, however, only had a positive influence on well-being for adults older than 63 years, but not for younger adults. Our findings contribute to a broader understanding of the consequences of different types of smartphone use on well-being across generations in the longitudinal context.